2014
DOI: 10.1007/s12550-014-0213-3
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Stachybotrys chartarum chemotype S in dried culinary herbs

Abstract: Stachybotrys (S.) chartarum is an omnipresent cellulolytic mould which produces secondary metabolites, such as the highly toxic macrocyclic trichothecenes. While it is known to occur in animal feed like hay and straw as well as in water-damaged indoor environments, there is little knowledge about the occurrence of S. chartarum and its secondary metabolites in food. The objective of the present study was to examine selected dried culinary herbs for the presence of S. chartarum chemotype S, to assess the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Stachybotrys (S.) spp. were detected on dead plant materials (e.g., herbs, straw, and hay) and other cellulosic substrates (Biermaier et al 2015;El-Kady and Moubasher 1982). Due to its high cellulolytic potential, Stachybotrys spp.…”
Section: Introductionmentioning
confidence: 99%
“…Stachybotrys (S.) spp. were detected on dead plant materials (e.g., herbs, straw, and hay) and other cellulosic substrates (Biermaier et al 2015;El-Kady and Moubasher 1982). Due to its high cellulolytic potential, Stachybotrys spp.…”
Section: Introductionmentioning
confidence: 99%
“…and two reference strains (IBT40293; ATCC34916)(available at ATCC (American Type Culture Collection), IBT Culture Collection of Fungi, Denmark and Culture Collection of the Chair of Food Safety, Faculty of Veterinary Medicine, Ludwig-Maximilians-University Munich). SB01a was isolated from oregano [ 3 ], S16St. from straw, IBT40293 from building materials [ 32 ] and ATCC34916 from oats.…”
Section: Methodsmentioning
confidence: 99%
“…Stachybotrys (S.) chartarum is the most frequently isolated species of the genus Stachybotrys [ 1 , 2 ] and had been isolated from dead plant materials (e.g., herbs, straw, and hay) and other cellulosic, and water damaged substrates (e.g., wallpaper, plasterboard, or wooden lining) [ 3 , 4 , 5 , 6 ]. The species S. chartarum can be further subdivided into three genotypes, the highly cytotoxic genotype S that produces macrocyclic trichothecenes (MCT), the low cytotoxic genotype A that produces atranone and the recently described genotype H that produces phenylspirodrimanes, but no macrocyclic trichothecenes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most research on mycotoxins focused on regulated mycotoxins. The recent unexpected discovery of the fungus Stachybotrys chartarum in culinary herbs (Biermaier et al 2015 ) showed that the scope has to be broadened: S. chartarum , so far known mainly from water-damaged walls, produces macrocyclic trichothecenes of higher acute toxicity than any regulated mycotoxin. Highly toxic metabolites of the fungus Stenocarpella maydis recently discovered in maize grains provide another example of toxicologically relevant non-regulated mycotoxins in food (Rogers et al 2014 ).…”
Section: Implications and Outlookmentioning
confidence: 99%